A Complete Genome Sequence of the Wood Stem Endophyte Bacillus velezensis BY6 Strain Possessing Plant Growth-Promoting and Antifungal Activities. (31st January 2021) - Zhang, Ping; Diao, Jian; Xie, Guangqiang; Ma, Ling; Wang, Lihai
Abstract : An endophytic bacterium Bacillus velezensis BY6 was isolated from the wood stems of healthy Populus davidiana × P. alba var. pyramidalis (PdPap). The BY6 strain can inhibit pathogenic fungus Alternaria alternate in PdPap and promote growth of PdPap seedlings. In the present study, we used the Pacific Biosciences long-read sequencing platform, a single-molecule real-time (SMRT) technology for strain BY6, to perform complete genome sequencing. The genome size was 3, 898, 273 bp, the number of genes was 4, 045, and the average GC content was 47.33%. A complete genome of strain BY6 contained 110 secondary metabolite gene clusters. Nine of the secondary metabolite gene clusters exhibited antifungal activity and promoted growth functions primarily involved in the synthesis of surfactin, bacteriocins, accumulated iron ions, and related antibiotics. Gene clusters provide genetic resources for biotechnology and genetic engineering, and enhance understanding of the relationship between microorganisms and plants.